2019
DOI: 10.1002/ajoc.201900409
|View full text |Cite
|
Sign up to set email alerts
|

Copper‐Catalyzed Selective Cross‐Couplings of Propargylic Ethers with Aryl Grignard Reagents

Abstract: The cross-coupling reactions of propargylic ethers with aryl Grignard reagents were achieved by using a copper catalyst. The method presents a practical and highly selective approach for the synthesis of propargyl derivatives by using ethyl salicylate as a directing leaving group, which highlights the advantages of its easy preparation and recovery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…In contrast to the asymmetric synthesis, α‐substitution reactions of enantiomerically enriched propargylic alcohol derivatives have been reported. Substrates/reagent systems published to date are ammonium salt/ArMgBr/Cu cat., [7] salicylate/ArMgCl/Cu cat., [8] ester/cuprate, [9] bromide/heteroaryl cuprate, [10] and sulfonate/TMSCF 3 /Cu cat./KF [11] . In addition, indirect methods to access α‐substituted acetylenes have been published [12] .…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to the asymmetric synthesis, α‐substitution reactions of enantiomerically enriched propargylic alcohol derivatives have been reported. Substrates/reagent systems published to date are ammonium salt/ArMgBr/Cu cat., [7] salicylate/ArMgCl/Cu cat., [8] ester/cuprate, [9] bromide/heteroaryl cuprate, [10] and sulfonate/TMSCF 3 /Cu cat./KF [11] . In addition, indirect methods to access α‐substituted acetylenes have been published [12] .…”
Section: Introductionmentioning
confidence: 99%
“…Li and co‐workers reported the copper‐catalyzed substrate‐directed cross‐coupling reaction of internal alkyne‐containing propargylic ethers with aryl Grignard reagents (Scheme 12). [23] In this study, the authors showed a single example for the stereospecific variants of the transformation. The reaction of the enantioenriched propargylic ether (97% ee) with phenylmagnesium chloride proceeded in the presence of copper bromide (5 mol%) to give the desired arylation product in 68% yield with 98% ee.…”
Section: Asymmetric Propargylic Substitution Of Propargylic Alcohol D...mentioning
confidence: 88%
“…[15], salicylate/ArMgCl/Cu cat. [16], bromide/heteroaryl cuprate [17], and sulfonate/TMSCF 3 /Cu cat./KF [18]. The α-substitution using racemic substrates was reported as well [19][20][21][22].…”
Section: Introductionmentioning
confidence: 89%